2017
DOI: 10.1142/s0219686717500135
|View full text |Cite
|
Sign up to set email alerts
|

Form Error Evaluation of Noncontact Scan Data Using Constriction Factor Particle Swarm Optimization

Abstract: Form error evaluation of manufactured parts is one of the crucial aspects of precision coordinate metrology. With the advent of technology, the noncontact data acquisition techniques are replacing the conventional machines like coordinate measuring machine (CMM). This paper presents an optimization technique to evaluate minimum zone form errors, namely straightness, circularity,°atness and cylindricity using constriction factor-based particle swarm optimization (CFPSO) algorithm. Addition of constriction facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…ABC has a slow convergence rate, easy to fall in local optimum, and is difficult to find the best out of available feasible solutions. PSO is widely employed to solve the continuous problems because of the simplicity of concept and fewer parametric settings than other population-based optimization algorithms 14 , 15 .…”
Section: Introductionmentioning
confidence: 99%
“…ABC has a slow convergence rate, easy to fall in local optimum, and is difficult to find the best out of available feasible solutions. PSO is widely employed to solve the continuous problems because of the simplicity of concept and fewer parametric settings than other population-based optimization algorithms 14 , 15 .…”
Section: Introductionmentioning
confidence: 99%
“…By comparing the accuracy and convergence time of the two advanced optimization algorithms, it was found that the two algorithms have obtained similar results, while TLBO takes a higher calculation time in comparison to PSO. Pathak [32] applied the constriction factor PSO (CFPSO) algorithm for evaluating different form errors, including minimum zone roundness. The constriction factor was added to the group velocity updating equation to enhance the exploration in initial iterations.…”
Section: Introductionmentioning
confidence: 99%
“…The addition of the constriction factor contributes in the CFPSO's convergence attribute being accelerated. For each form issue, a simple minimum zone objective function is mathematically formulated and finally optimized using the proposed CFPSO [31]. PSO with moving particles (MP-PSO) has been reported [32], where some particles have the ability to move on a scale-free network and also variate the collaboration form thru the search space.…”
Section: Introductionmentioning
confidence: 99%
“…The main aim of this work aim is to control the impact of the previous velocity and to control the particle's behavior of exploration as well as exploitation. Introduction of the inertia-weight improves the performance of PSOs in the terms of convergence speeds and superiority in results [31]. After the inclusion of inertia-weight ( ), the velocity equation is updated as…”
Section: Introductionmentioning
confidence: 99%